Strategies for the evaluation of existing timber structures: Challenges, problems and solutions - Saporiti Machado, J. (2016)
To perform a reliable assessment of existing timber structures it is necessary to take into account a multiscale and time dependent behaviour. Unfortunately simple and straight forward analysis usually conducted uses only the information available to the design of new timber structures. In the last decade some important advances were made in the fields of guidelines for the assessment of existing timber structures, new survey techniques (including semi-destructives techniques), new data treatment models and regulations. However the uncertainty about the wood material and its properties, the behaviour of timber connections and the way the different survey methods can be efficiently used makes extremely difficult to provide reliable data to the engineer responsible for performing a safety and serviceability analysis of an existing timber structure. As a result of this procedure the final decision is often based on high cost repair/reinforcement works or the demolition of the entire structure even if that structure performed satisfactorily for decades. The present paper discusses different aspects to take into account while performing a survey to a timber structure, detailing some procedures to be followed to obtain information on relevant variables (strength of structural members and connections) and possibilities to address the effect of biodeterioration, time-dependent problems and available data treatments methods. The discussion is supported by recent results on the analysis of structural timber members and new paths based on activities foreseen to be conducted within a research project that will be launched in 2016.